The Inner Conflict Of The Main Characters In Maman Suherman's Novels - Hehanussa, St Naisa; Nuryatin, Agus; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
In Maman Suherman's novels, there are inner conflicts of the main characters. Sources of data used in this study are novels by Maman Suherman entitled Re, Perempuan, and Bapakku Indonesia. The purpose of this study is divided into three analyzes, namely (a) a description of the inner conflict of the main character in Maman Suherman's novels, (b) the cause of the inner conflict of the main character in Maman Suherman's novels, (c) resolving the inner conflict of the main character in the novel. - a novel by Maman Suherman. The qualitative descriptive method of Kurt Lewin's theory uses a hermeneutic approach. Based on the results of data analysis obtained; (a) Re novel consists of four inner conflicts, first there are two events with an (approach-approach conflict). The second, third, and fourth inner conflicts are three events with an (approach-avoidance conflict), (b) the novel Perempuan which consists of three conflicts, namely the approach-away inner conflict consisting of one event. The second is the near-distant conflict where there is one event. The third conflict is moving away, there is one event, (c) the novel Bapakku Indonesia, consists of three inner conflicts. The first is a close-away conflict consisting of one event. The second and third inner conflicts are (apporach-approach conflicts) which have one event each.